HOTEL BUSINESS IN MODERN CONDITIONS: CURRENT TRENDS AND DEVELOPMENT ISSUES - Mukhtarov, Botir (Science technology&Digital finance, 2024)
The hotel business is a rapidly developing industry, even in the context of an economic crisis and an unstable political situation. The article presents an analysis of the global market of the hotel industry, development trends in the current business situation. The role of the hospitality industry in the world economic system will be considered. An analysis of the reasons for the high attractiveness and profitability of the hotel business is presented. Innovative trends and main problems of the development of the hotel industry in Russia and the world were studied.